Experimental and Applied Mechanics, Volume 6 Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This the sixth volume of six from the Annual Conference of the Society for Experimental Mechanics, 2010, brings together 128 chapters on Experimental and Applied Mechanics. It presents early findings from experimental and computational investigations including High Accuracy Optical Measurements of Surface Topography, Elastic Properties of Living Cells, Standards for Validating Stress Analyses by Integrating Simulation and Experimentation, Efficiency Enhancement of Dye-sensitized Solar Cell, and Blast Performance of Sandwich Composites With Functionally Graded Core.
Keywords: Engineering; Mechanics; Mechanics, applied; Materials; Engineering; Theoretical and Applied Mechanics; Mechanics; Materials Science, general